Considering the Private Animal and Damages - Richard L. Cupp Jr. (Washington University Law Review, 2021)
Since 2018, private law damages claims seeking to place animals in the role of plaintiffs have––in dramatic fashion––moved from academic debate to high-profile litigation. Focusing on two recent cases, this short Article asserts that lawsuits seeking to make animals plaintiffs in damages actions are much more than flashy news fodder; they raise profound policy issues that courts will struggle with into the foreseeable future. The most recent prominent case, Justice v. Vercher, is ongoing litigation seeking to designate a severely neglected horse as the plaintiff in a tort damages lawsuit against the horse’s owner. The second case, Naruto v. Slater, unsuccessfully sought to designate a monkey as the plaintiff in a copyright infringement lawsuit. Both cases illuminate significant implications of seeking to designate animals as plaintiffs in private law damages lawsuits. Thankfully, societal concern about animal welfare is rapidly increasing, although more needs to be done to protect animals. But efforts like Vercher and Narutorepresent a societally harmful approach to animal protection. Such cases may continue to fail in the short term, but regardless of short-term failure or success, analogous lawsuits are nevertheless likely to proliferate over time because the stakes are so high––success could be a back door to breaking down legal barriers between humans and animals. Further, as societal views regarding animals quickly evolve, the possibility of misguided rulings creating dangerous animal legal personhood through such lawsuits is real.
Keywords: Justice v. Vercher; Naruto v. Slater; Tort law; Animal protection; Legal personhood; Animal plaintiffs